Rasionalitas Pengambilan Keputusan Feeder Dan Surabaya Bus Terhadap Nasib Sopir Angkutan Umum Konvensional Menurut Teori Rasionalitas Max Weber - Dzugharieb Cheyna Fillah; Aisa Tria Sabela; Revienda Anita Fitrie (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
The city of Surabaya with a population that has high mobility certainly requires transportation to support population activities. As a city with a high population, the city of Surabaya certainly faces various problems in public transportation services, one of which is congestion. To overcome this problem, the Surabaya City Government launched the Suroboyo bus and Wira Wiri fleets as alternative public transportation to overcome vehicle density in the city of Surabaya. However, the existence of Suroboyo Bus and Wira Wiri Suroboyo as public transportation that covers almost the entire area of ​​Surabaya City, leaves questions about what will happen to drivers of conventional public transportation such as angkot or lyn which have previously been the choice of public transportation for the people of Surabaya City. It cannot be denied that the existence of Suroboyo Bus and Wira Wiri Suroboyo has caused a decrease in demand for conventional public transportation passengers. The aim of this research is to describe the rationality of Surabaya Bus and Wira Wiri decision making regarding conventional public transportation according to Max Weber's theory of rationality. This research uses a qualitative method with a descriptive approach. In research using literature or literature studies, the results can be obtained that Surabaya Bus and Wira Wiri's decision making regarding conventional public transportation does not fully fulfill the forms of rationality proposed by Max Weber.